1991
DOI: 10.1210/endo-129-2-591
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Diazepam Binding Inhibitor in Rat Adrenal Gland by Adrenocorticotropin

Abstract: Diazepam binding inhibitor (DBI) is a 9-kDa polypeptide that was initially isolated from rat brain and subsequently found to be present in several peripheral tissues. DBI is particularly abundant in steroidogenic tissues, such as the adrenal glands and testes, which also contain a high concentration of peripheral/mitochondrial benzodiazepine receptors (MBRs). Because occupancy of adrenal MBRs with DBI results in increased steroidogenesis, we have investigated the relation between ACTH, DBI, and the MBR in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1992
1992
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…Initially, we determined whether ACTH could rapidly increase DBI or MDR expression in adrenal cortex. Our results, in agreement with those already described (38,39), provide clear evidence that in the rat adrenal gland, the immediate steroidogenic action of ACTH is not associated with'changes in DBI or MDR expression. Treatment of hypophysectomized rats, 1 day after surgery, with ACTH failed to affect immediately (up to 1.5 hr) the amounts of adrenal DBI-LI or MDR or the concentrations of their mRNAs.…”
Section: Discussionsupporting
confidence: 93%
“…Initially, we determined whether ACTH could rapidly increase DBI or MDR expression in adrenal cortex. Our results, in agreement with those already described (38,39), provide clear evidence that in the rat adrenal gland, the immediate steroidogenic action of ACTH is not associated with'changes in DBI or MDR expression. Treatment of hypophysectomized rats, 1 day after surgery, with ACTH failed to affect immediately (up to 1.5 hr) the amounts of adrenal DBI-LI or MDR or the concentrations of their mRNAs.…”
Section: Discussionsupporting
confidence: 93%
“…It has, however, been reported that trophic hormone replacement in hypophysectomized rats increased DBI levels in the adrenal (176) and in the Leydig cells (114). Increases in DBI levels in these experiments were observed only after at least 2 h subsequent to the administration of hormones.…”
Section: Steroid Productscontrasting
confidence: 59%
“…Recently, DBI itself and its two major process¬ ing products DBI 33-550 and DBI 17-50 have recently been found to stimulate pregnenolone formation in adrenocortical and testicular mitochondria (Papadopoulos, Berkovich, Krueger et al 1991 ). It is interesting that DBI in the adrenal appears to be under the control of ACTH, the tissue content declines after hypophysectomy and increases with ACTH treatment (Massotti, Slobodyanski, Konkel et al 1991). …”
Section: Diazepam-binding Inhibitor/endozepinementioning
confidence: 99%
“…Although initially this seemed a strong possibility, there are a number of facts which argue against DBI having a unique role, of which probably the most telling is that the time-course of its appearance after ACTH treatment does not correlate with steroidogenic response either in vitro or in vivo (Massotti et al 1991;Brown, Hall, Shoyab & Papadopoulos, 1992). It may be simply that process¬ ing of the molecule is required, since there is some evidence that the smaller DBI-derived peptides are more active (Papadopoulos et al 1991 ).…”
Section: Significance Of Dbi and The Benzodiazepine Receptorsmentioning
confidence: 99%